Assessing Students’ Chemical Understanding on Classification of Matters - Sitna Windia Risqi; Iva Nur Azizah; Ifah Silfianah (Universitas Negeri Malang, 2021)
Chemistry subject is often considered difficult by some students, it is one of the features to lead misunderstanding of chemistry concept. Material is a basic concept that needs to figure out especially to make easier the concept of classifying material. The data analyzed using descriptive quantitative approaches with test items. The resets displayed that most of the study got difficulties differentiating elements, compounds, and molecules. They still gained complaints to categorized molecular elements and elements, molecular compounds and compounds, and atoms and ions.ReferencesAdadan, Emine (2014) Investigating the influence of pre-service chemistry teachers’ understanding of the particle nature of matter on their conceptual understanding of solution chemistry, Chemistry Education Research and Practice, 219-238.Andersson, B. (1990). Pupils conceptions of matter and its transformation (age12- 16). Studies in Science Education , 18, 53-85.Anshory, Irfan. 2000. Acuan Pelajaran Kimia Kelas 1 SMU. Jakarta : Erlangga.Adisendjaja, Yusuf Hilmi, Oom romlah (2007) Identifikasi kesalahan dan miskonsepsi buku teks biologi SMU, Seminar Nasional Pendidikan Biologi dan Biologi, 1-13.Avci, Filiz, Burci Acar Sesen, Fatma Gulay Kirbaslar (2014) Determination of seventh grade students’ understanding of certain chemistry concepts, ScienceDirect, 152 ( 602-606).Brady,E James. (1994). Kimia Universitas. Jakarta : Erlangga.Dahar, Ratna Wilis. (1989). Teori – teori Belajar. Jakarta. Erlangga.Alighiri, Dante. Apriliana Drastisianti, dan Endang Susila Ningsih. (2018). Pemahaman Konsep Siswa Materi Larutan Penyangga Dalam Pembelajaran MultipleRepresentasi. Jurnal Inovasi Pendidikan Kimia. Vol 12. No 2. Hal 2192-2200.Duit, R., Gropengiesser, H., Kattmann, U., Komorek, M., & Parchman, I. (2012). The model of educational reconstruction-a framework for improving teaching and learning science. In D. Jorde & J. Dillion (Eds.) Science education research and practice in Europe: Restrospective and prospective. , 13-47.Hanson, R., Sam, A., & Antwi, V. (2012). Misconceptions of understanding chemistry teachers about hybridisation. African Journal of Educational Studies in Mathematics and Science. , 10, 12-14.Jannah, M., Ningsih, P., dan Ratman. (2016). Analisis Miskonsepsi Siswa Kelas XI SMA Negeri 1 Banawa Tengah Pada Pembelajaran Larutan Penyangga Dengan CRI (Certainty Of Response Index). Jurnal Akademika Kimia. Vol 5. No 2. Hal 85-90.Maghfiroh, L., Santosa, dan Suryadharma, I. B., (2016). Identifikasi Tingkat Pemahaman Konsep Stoikiometri Pada pereaksi Pembatas Dalam Jenis-Jenis Reaksi Kimia Siswa Kelas X MIA SMA Negeri 4 Malang. (J-PEK) Jurnal Pembelajaran Kimia. Vol 1. No 2, Hal 32-37.Nakhleh, Mary B (1992) Why some students don't learn chemistry: Chemical misconceptions, Journal of Chemical Education, vol. 69.Nurhafizah, Husna Amalya Melati, Rahmat Rasmawan (2017) Deskripsi pemahaman konsep materi dan perubahannya siswa kelas x smk smti pontianak, 1-11.Sam, arkoful, kai niebert, ruby hanson, ankrah kwarteng twumasi (2015) the model of educational reconstruction: scientists’ and students’ conceptual balances to improve teaching of coordination chemistry in higher education, International Journal of Academic Research and Reflection, Vol. 3 (7), 67-77.Saputro, Agung Nugroho Catur dan Irwan Nugraha. 2007. Kimia : Seandainya Kehidupan tanpa Kimia? Jilid 1. Buku pelajaran kimia untuk siswa SMA/MA kelas X. Jakarta : Direktorat Pendidikan Madrasah, Direktorat Jenderal Pendidikan Islam, Departemen Agama RI.Stavy, R. (2008). Learning Science in the Schools: Research Informing Practice. New Jersey: Lawrence Erlbaum: Hillsdale.Sudijono, Anas. (2013). Pengantar Evaluasi pendidikan. PT. Raja Grafindo Persada. JakartaSukmadinata, N.S (2011). Metode Penelitian Pendidikan. Bandung:Remaja RosadakaryaSyukri. (1999). Kimia Dasar Jilid 1. Bandung: ITB.Taber, K. S. (2002). Chemical misconceptions-Preventions, diagnosis and cure. (Vol. 1). London: Royal Society of Chemistry.Yakubi, Malik, Zulfadli, Latifah Hanum, Menganalisis Tingkat Pemahaman Siswa pada Materi Ikatan Kimia Menggunakan Instrumen Penilaian Four-Tier Multiple Choice (Studi Kasus pada Siswa Kelas X SMA Negeri 4 Banda Aceh), Jurnal Ilmiah Mahasiswa Pendidikan Kimia (JIMPK), Vol 2 . No.1 (19-26).